CO2 capture and utilization integrated bifunctional material as well as preparation method and application thereof

Bifunctional materials are prepared by doping transition metal elements into chromium-based spinel catalysts, combining calcium-based adsorbents and metal oxide-doped solngeons, which solves the weak CO2 capture performance and stable cycle in the prior art. The poor performance problem has achieved efficient CO2 capture and ethylene preparation.

CN119425611APending Publication Date: 2025-02-14NAT ENERGY COAL & COKING GRP CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411461669.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the CO2 capture and ethane oxidation and dehydrogenation process, existing dual-functional materials have problems such as weak CO2 capture performance, ethane oxidation and dehydrogenation performance, and severe carbon deposits in the material are prone to deactivation, resulting in poor cycle stability.

Method used

By doping transition metal elements such as Fe, Co, Ni, Cu and Zn into the chromium-based spinel catalyst, changing the charge distribution, increasing the number of ethane active sites, reducing the energy barrier of CO2 and ethane activation, and combining calcium Bifunctional materials are prepared by sol-gel method of base adsorbent and metal oxide doped with sol-gel.

Benefits of technology

It significantly improves CO2 capture performance, ethane oxidative dehydrogenation performance and cycle stability, and achieves efficient integration of CO2 capture and ethylene preparation, and does not require high pressure or sealed conditions, making it suitable for large-scale industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425611A_ABST
    Figure CN119425611A_ABST
Patent Text Reader

Abstract

The invention relates to a CO2 capture and utilization integrated bifunctional material as well as a preparation method and application thereof. The CO2 capture and utilization integrated bifunctional material comprises a mixture of an adsorbent and a catalyst in a mass ratio of 1: (0.5-1.5), the adsorbent is a calcium-based adsorbent or a calcium-based adsorbent doped with a metal oxide; the catalyst is chromium-based spinel doped with transition metal elements. The transition metal element is doped into the chromium-based spinel, so that the charge distribution can be changed, the number of ethane active sites can be increased, the activation reaction energy barrier of CO2 and ethane can be reduced, the oxidative dehydrogenation of ethane is facilitated, and the ethylene yield is good. According to the invention, harsh conditions such as high pressure or sealing are not needed, the preparation method is simple, toxic and harmful wastes are not generated in the production process, and the method is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of dual-function materials, and specifically relates to a CO2 capture and utilization integrated dual-function material and a preparation method and application thereof. Background Art

[0002] Ethylene is an important chemical raw material and is regarded as an important indicator of a country's chemical development level. In recent years, CO2-ethane oxidative dehydrogenation has attracted much attention. This method breaks the thermodynamic limitations of the original ethane dehydrogenation and drives the reaction in a direction that is favorable for ethylene production. At the same time, CO2 is a mild oxidant that can reduce the over-oxidation of ethylene during the reaction and improve ethylene selectivity.

[0003] It is found that in the traditional CO2-ethane oxidative dehydrogenation process to produce ethylene, it is difficult to continuously introduce a large amount of high-purity CO2 at a stable concentration in industry, which requires high operating costs or the support of carbon capture technology. Therefore, a calcium oxide-based adsorbent mixed with different ethane dehydrogenation catalysts to form a dual-functional material (DFM) has received increasing attention. The calcium oxide adsorbent in the dual-functional material mainly plays the role of capturing and decomposing CO2, while the catalytic performance of CO2-ODHE mainly depends on the catalyst in the composite material. Therefore, the development of an efficient CO2-ODHE catalyst is the key to improving the efficiency of ethylene production.

[0004] Among many catalysts, spinel catalysts have good catalytic properties and have broad application prospects in the CO2-ethane oxidative dehydrogenation process to ethylene. Although predecessors have done a lot of work on the basic research of spinel catalysts and have achieved many phased research results, this dual-functional material still has problems such as weak CO2 capture performance, ethane oxidative dehydrogenation performance that does not meet expectations, and severe carbon deposition and easy deactivation of the material, resulting in poor cycle stability, which seriously restricts the practical application of this technology. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a CO2 capture and utilization integrated dual-functional material and a preparation method and application, and solve the technical problems of weak CO2 capture performance and poor cycle stability in the prior art.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides an integrated dual-functional material for CO2 capture and utilization, comprising a mixture of an adsorbent and a catalyst in a mass ratio of 1:(0.5-1.5); the adsorbent is a calcium-based adsorbent or a calcium-based adsorbent doped with a metal oxide; and the catalyst is a chromium-based spinel doped with a transition metal element.

[0007] In a second aspect, the present invention provides a method for preparing an integrated dual-functional material for CO2 capture and utilization, comprising the following steps: mixing an adsorbent and a catalyst in proportion.

[0008] In a third aspect, the present invention provides an application of the above-mentioned dual-functional material in CO2 capture and ethane oxidative dehydrogenation to ethylene.

[0009] In a fourth aspect, the present invention provides an integrated application of the above-mentioned dual-functional material in CO2 capture and ethane reforming / cracking.

[0010] Compared with the prior art, the beneficial effects of the present invention include: 1. The present invention dopes transition metal elements into chromium-based spinel, which can change the charge distribution, increase the number of ethane active sites, reduce the energy barrier of CO2 and ethane activation reaction, and facilitate the occurrence of ethane oxidative dehydrogenation; 2. The CO2 capture and utilization integrated dual-function material prepared by the present invention is a dual-function material that can simultaneously realize CO2 capture and ethylene production, has good CO2 capture effect, good cycle stability, can be recycled, and has a good ethylene yield. The preparation method is simple and suitable for large-scale industrial applications; 3. The present invention does not require harsh conditions such as high pressure or airtightness, and the production process does not produce toxic or harmful waste, which is a zero-emission and pollution-free technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 The present invention is a summary of the gas concentration curves of the integrated dual-functional material for CO2 capture and conversion during five cycles and the performance of the integrated ethylene production by isothermal capture and conversion of CO2 (including CO2 conversion rate, ethane conversion rate, ethylene selectivity, and ethylene yield); wherein, (a) Comparative Example 1 (a1 is the gas concentration curve, a2 is the performance of the integrated ethylene production by isothermal capture and conversion of CO2), (b) Example 1, (c) Example 2; Figure 2 It is a summary of the gas concentration curves and CO2 conversion rate, ethane conversion rate, ethylene selectivity, and ethylene yield of CO2 capture using integrated dual-functional materials in 5 cycles in Examples 3-5 of the present invention; wherein (d) is Example 3, (e) is Example 4, and (f) is Example 5; Figure 3 These are the test results of the best dual-functional material in Example 5 of the present invention under isothermal conditions at 650°C for cyclic regeneration, where (a) is the CO2 conversion rate, (b) is the ethane conversion rate, (c) is the ethylene selectivity, and (d) is the ethylene yield. DETAILED DESCRIPTION

[0012] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0013] In view of the problems of existing bifunctional materials such as weak CO2 capture performance, ethane oxidative dehydrogenation performance not meeting expectations, severe carbon deposition and easy deactivation of materials resulting in poor cycle stability, the present invention provides an integrated bifunctional material for CO2 capture and utilization, a preparation method and an application. By doping transition metal elements into the spinel catalyst, the CO2 capture performance, ethane oxidative dehydrogenation performance and cycle stability of the bifunctional material are improved.

[0014] In a first aspect, the present invention provides an integrated dual-functional material for CO2 capture and utilization, comprising a mixture of an adsorbent and a catalyst in a mass ratio of 1:(0.5-1.5); the adsorbent is a calcium-based adsorbent or a calcium-based adsorbent doped with a metal oxide; and the catalyst is a chromium-based spinel doped with a transition metal element.

[0015] Preferably, the calcium-based adsorbent includes one or more of calcium oxide, calcium hydroxide, calcium carbonate and slaked lime, and more preferably calcium oxide.

[0016] Preferably, in order to improve the CO2 capture cycle stability of the adsorbent, when the adsorbent is a calcium-based adsorbent doped with metal oxides, the metal oxides include one or more of CeO2, MgO and Al2O3, and the mass doping ratio of the metal oxides in the adsorbent is less than 30%.

[0017] Preferably, the transition metal elements doped in the catalyst include one or more of Fe, Co, Ni, Cu and Zn, and the molar doping ratio of the transition metal elements in the catalyst is less than 50%; that is, the molar proportion of the transition metal elements in each mole of chromium-based spinel. The molar doping ratio can also be understood as the ratio of the molar amount of the transition metal element to the total molar amount of the transition metal element and the magnesium element in the catalyst.

[0018] Preferably, the particle size of the integrated dual-function material used for CO2 capture is 40-60 mesh.

[0019] In a second aspect, the present invention provides a method for preparing an integrated dual-functional material for CO2 capture and utilization, comprising the following steps: mixing an adsorbent and a catalyst in proportion.

[0020] Preferably, in the adsorbent, the preparation steps of the calcium-based adsorbent doped with metal oxides include: adding citric acid to a solution containing calcium nitrate and metal nitrate, heating and stirring until it is in a gel state, and aging to obtain a calcium-based precursor; calcining the calcium-based precursor at 850-950°C for 1.5-2.5h, and then grinding and screening to obtain a calcium-based adsorbent doped with metal oxides. The present invention adopts the above-mentioned sol-gel method to prepare the calcium-based adsorbent doped with metal oxides, so that the adsorbent CaO and the metal oxide are mixed more evenly.

[0021] Further preferably, the ratio of the total molar amount of calcium ions in calcium nitrate and metal ions in metal nitrate to the molar amount of citric acid is 1:(0.99-1.01); in the preparation steps of the calcium-based adsorbent doped with metal oxide: the heating temperature for heating and stirring until the gel state is 75-85°C; the aging is aging at 100-110°C for 11-13 hours; the heating rate during calcination is 4-6°C / min.

[0022] Preferably, the preparation steps of the chromium-based spinel doped with transition metal elements in the catalyst include: dissolving transition metal nitrate, magnesium nitrate, chromium nitrate and citric acid in deionized water, heating and stirring until they are in a gel state, and obtaining a catalyst precursor through aging; calcining the catalyst precursor at 850-950°C for 3.5-4.5h, and then grinding and screening to obtain the chromium-based spinel doped with transition metal elements.

[0023] Further preferably, the molar ratio of transition metal nitrate, magnesium nitrate, chromium nitrate and citric acid is 1:1:4:6; the transition metal nitrate includes one or more of ferrous nitrate, cobalt nitrate, nickel nitrate, copper nitrate and zinc nitrate; the molar volume ratio of transition metal nitrate and deionized water is 6.25mmol: (7-12)mL. The present invention can obtain X by controlling the amount of each raw material. 0.5 Mg 0.5 Cr2O4 (X=Mg, Fe, Co, Ni, Cu, Zn) spinel catalyst. The present invention controls the molar ratio of each raw material to synthesize the spinel catalyst and improve the catalytic performance of the obtained material.

[0024] Further preferably, in the preparation step of chromium-based spinel doped with transition metal elements, the heating temperature for heating and stirring until it is in a gel state is 75-85°C; the aging is carried out at 140-160°C for 11-13 hours; and the heating rate during calcination is 4-6°C / min.

[0025] In a third aspect, the present invention provides an integrated application of the above-mentioned dual-functional material in CO2 capture and ethane oxidative dehydrogenation to ethylene.

[0026] Preferably, when used in CO2 capture and ethane oxidative dehydrogenation to ethylene, the transition metal elements doped in the catalyst include one or more of Fe, Co, Cu and Zn.

[0027] In a fourth aspect, the present invention provides an integrated application of the above-mentioned dual-functional material in CO2 capture and ethane reforming / cracking.

[0028] Preferably, in the integrated application of CO2 capture and ethane reforming / cracking, the transition metal element doped in the catalyst includes Ni.

[0029] The main mechanism of action and advantages of the present invention are: (1) The present invention uses transition metal elements such as Fe, Co, Ni, Cu and Zn to change the charge distribution of the spinel catalyst by using their strong electronegativity, thus creating more coordinated unsaturated Cr 3+ To improve the conversion rate of ethane; at the same time, the ethane oxidative dehydrogenation that occurs in the CO2 utilization stage is essentially a charge transfer process, and doping with transition metal elements can change the active site Cr 3+ The charge density of the ions helps to improve the conversion activity of ethane and CO2.

[0030] (2) The present invention forms a complex by adding citric acid and other raw materials. When calcined at high temperature, the complex will decompose and release CO2 and H2O to enrich the pore structure of the adsorbent and the catalyst. At the same time, since the sol-gel method adopts solution mixing, the element distribution of the sample is uniform, which can produce more active sites, which is conducive to the capture of CO2 and the oxidative dehydrogenation of ethane to produce ethylene.

[0031] The present invention is further described in detail below through specific examples.

[0032] Example 1 The Fe-doped CO2 capture and conversion integrated dual-functional material, the preparation method of which comprises the following steps: Step 1, take 10g Ca(NO3)2 and 1.52g Ce(NO3)3·6H2O and dissolve them in 100mL deionized water, add 13.55g C6H8O7·H2O to the solution, then continue to stir the solution at 80℃ until it is in a gel state, and age it at 105℃ for 12 hours. Then, the above precursor is heated to 900℃ at 5℃ / min and calcined for 2 hours. The calcined calcium-based adsorbent is ground to 40-60 mesh to obtain a suitable calcium-based adsorbent.

[0033] Step 2, 1.125g Fe(NO3)2, 1.6g Mg(NO3)2·6H2O, 10g Cr(NO3)3·9H2O and 7.88g C6H8O7·H2O were dissolved in 9mL deionized water, the mixed solution was stirred at 80°C until it was in a gel state, and aged at 150°C for 12 hours. Subsequently, the above precursor was heated to 900°C at 5°C / min and calcined for 4 hours. The calcined chromium-based spinel catalyst was ground to 40-60 mesh, and finally Fe with a moderate particle size was obtained. 0.5 Mg 0.5 Cr2O4 spinel catalyst.

[0034] Step 3: Finally, the calcium-based adsorbent obtained in step 1 and the Fe 0.5 Mg 0.5 Cr2O4 spinel catalyst was mixed in a mass ratio of 1:1 to obtain a calcium-based bifunctional composite material.

[0035] Example 2 The preparation method of the CO2 capture and conversion integrated dual-functional material doped with Co element comprises the following steps: Step 1, take 10g Ca(NO3)2 and 1.52g Ce(NO3)3·6H2O and dissolve them in 100mL deionized water, add 27.1g C6H8O7·H2O to the solution, then continue to stir the solution at 80℃ until it is in a gel state, and age it at 105℃ for 12 hours. Then, the above precursor is heated to 900℃ at 5℃ / min and calcined for 2 hours. The calcined calcium-based adsorbent is ground to 40-60 mesh to obtain a suitable calcium-based adsorbent.

[0036] Step 2, 1.82 g Co(NO3)2·6H2O, 1.6 g Mg(NO3)2·6H2O, 10 g Cr(NO3)3·9H2O and 7.88 g C6H8O7·H2O were dissolved in 9 mL of deionized water, the mixed solution was stirred at 80 °C until it was in a gel state, and aged at 150 °C for 12 hours. Subsequently, the above precursor was heated to 900 °C at 5 °C / min for 4 hours, and the calcined chromium-based spinel catalyst was ground to 40-60 mesh, and finally Co with a moderate particle size was obtained. 0.5 Mg 0.5 Cr2O4 spinel catalyst.

[0037] Step 3: Finally, the calcium-based adsorbent obtained in step 1 and the Co obtained in step 2 0.5 Mg 0.5 Cr2O4 spinel catalyst was mixed in a mass ratio of 1:1 to obtain a calcium-based bifunctional composite material.

[0038] Example 3 The preparation method of the CO2 capture and conversion integrated dual-functional material doped with 50% Ni element comprises the following steps: Step 1, take 10g Ca(NO3)2 and 1.52g Ce(NO3)3·6H2O and dissolve them in 100mL deionized water, add 27.1g C6H8O7·H2O to the solution, then continue to stir the solution at 80℃ until it is in a gel state, and age it at 105℃ for 12 hours. Then, the above precursor is heated to 900℃ at 5℃ / min and calcined for 2 hours. The calcined calcium-based adsorbent is ground to 40-60 mesh to obtain a suitable calcium-based adsorbent.

[0039] Step 2, 1.82 g Ni(NO3)2·6H2O, 1.6 g Mg(NO3)2·6H2O, 10 g Cr(NO3)3·9H2O and 7.88 g C6H8O7·H2O were dissolved in 9 mL of deionized water, the mixed solution was stirred at 80°C until it was in a gel state, and aged at 150°C for 12 hours. Subsequently, the above precursor was heated to 900°C at 5°C / min and calcined for 4 hours. The calcined chromium-based spinel catalyst was ground to 40-60 mesh, and finally Ni with a moderate particle size was obtained. 0.5 Mg 0.5 Cr2O4 spinel catalyst.

[0040] Step 3, finally, the calcium-based adsorbent obtained in step 1 and the Ni obtained in step 2 0.5 Mg 0.5 Cr2O4 spinel catalyst was mixed in a mass ratio of 1:1 to obtain a calcium-based bifunctional composite material.

[0041] Example 4 The preparation method of the CO2 capture and conversion integrated dual-functional material doped with 50% Cu element comprises the following steps: Step 1, take 10g Ca(NO3)2 and 1.52g Ce(NO3)3·6H2O and dissolve them in 100mL deionized water, add 27.1g C6H8O7·H2O to the solution, then continue to stir the solution at 80℃ until it is in a gel state, and age it at 105℃ for 12 hours. Then, the above precursor is heated to 900℃ at 5℃ / min and calcined for 2 hours. The calcined calcium-based adsorbent is ground to 40-60 mesh to obtain a suitable calcium-based adsorbent.

[0042] Step 2, 1.51g Cu(NO3)2·3H2O, 1.6g Mg(NO3)2·6H2O, 10g Cr(NO3)3·9H2O and 7.88g C6H8O7·H2O were dissolved in 9mL deionized water, the mixed solution was stirred at 80°C until it was in a gel state, and aged at 150°C for 12 hours. Subsequently, the above precursor was heated to 900°C at 5°C / min and calcined for 4 hours. The calcined chromium-based spinel catalyst was ground to 40-60 mesh, and finally a Cu with a moderate particle size was obtained. 0.5 Mg 0.5 Cr2O4 spinel catalyst.

[0043] Step 3, finally, the calcium-based adsorbent obtained in step 1 and the Cu obtained in step 2 0.5 Mg 0.5 Cr2O4 spinel catalyst was mixed in a mass ratio of 1:1 to obtain a calcium-based bifunctional composite material.

[0044] Example 5 The preparation method of the CO2 capture and conversion integrated dual-functional material doped with 50% Zn element comprises the following steps: Step 1, take 10g Ca(NO3)2 and 1.52g Ce(NO3)3·6H2O and dissolve them in 100mL deionized water, add 27.1g C6H8O7·H2O to the solution, then continue to stir the solution at 80℃ until it is in a gel state, and age it at 105℃ for 12 hours. Then, the above precursor is heated to 900℃ at 5℃ / min and calcined for 2 hours. The calcined calcium-based adsorbent is ground to 40-60 mesh to obtain a suitable calcium-based adsorbent.

[0045] Step 2, 1.18g Zn(NO3)2, 1.6g Mg(NO3)2·6H2O, 10g Cr(NO3)3·9H2O and 7.88g C6H8O7·H2O were dissolved in 9mL deionized water, the mixed solution was stirred at 80°C until it was in a gel state, and aged at 150°C for 12 hours. Subsequently, the above precursor was heated to 900°C at 5°C / min for 4 hours, and the calcined chromium-based spinel catalyst was ground to 40-60 mesh, and finally Zn with a moderate particle size was obtained. 0.5 Mg 0.5 Cr2O4 spinel catalyst.

[0046] Step 3, finally, the calcium-based adsorbent obtained in step 1 and the Zn obtained in step 2 0.5 Mg 0.5 Cr2O4 spinel catalyst was mixed in a mass ratio of 1:1 to obtain a calcium-based bifunctional composite material.

[0047] Comparative Example 1 The preparation method of the undoped CO2 capture and conversion integrated dual-functional material comprises the following steps: Step 1, take 10g Ca(NO3)2 and 1.52g Ce(NO3)3·6H2O and dissolve them in 100mL deionized water, add 27.1g C6H8O7·H2O to the solution, then continue to stir the solution at 80℃ until it is in a gel state, and age it at 105℃ for 12 hours. Then, the above precursor is heated to 900℃ at 5℃ / min and calcined for 2 hours. The calcined calcium-based adsorbent is ground to 40-60 mesh to obtain a suitable calcium-based adsorbent.

[0048] Step 2: 3.2 g Mg(NO3)2·6H2O, 10 g Cr(NO3)3·9H2O and 7.88 g C6H8O7·H2O were dissolved in 9 mL deionized water, the mixed solution was stirred at 80°C until it was in a gel state, and aged at 150°C for 12 hours. Subsequently, the above precursor was heated to 900°C at 5°C / min and calcined for 4 hours, and the calcined chromium-based spinel catalyst was ground to 40-60 mesh, and finally a MgCr2O4 spinel catalyst with a moderate particle size was obtained.

[0049] Step 3, finally, the calcium-based adsorbent obtained in step 1 and the MgCr2O4 spinel catalyst obtained in step 2 are mixed in a mass ratio of 1:1 to obtain a calcium-based bifunctional composite material.

[0050] Comparative Example 2 The difference from Example 5 is that the calcium-based adsorbent and Zn in step 3 are 0.5 Mg 0.5 The mass ratio of the Cr2O4 spinel catalyst was adjusted to 1:0.2, 1:0.5, 1:1.5 or 1:2, and the other steps and conditions were the same as those in Example 5.

[0051] The results showed that with the increase of catalyst dosage, the ethylene yield tended to increase, but too much catalyst would lead to a decrease in the cyclic stability of the obtained bifunctional material. Therefore, a mass ratio of the adsorbent to the catalyst that was too high or too low would cause adverse effects. In the present invention, a mixture of the adsorbent and the catalyst in a mass ratio of 1: (0.5-1.5) is preferred.

[0052] Performance Testing The undoped comparative example 1 and the calcium-based bifunctional materials doped with transition metal elements of Examples 1 to 5 of the present invention were subjected to the CO2 isothermal capture and conversion integrated ethylene production performance test in a fixed bed quartz reactor. The CO2 isothermal capture and conversion integrated pretreatment / capture / conversion conditions were as follows: pretreatment: 650°C, 30min, 100 vol.% N2; adsorption: 650°C, 30min, 15vol.% CO2; conversion: 650°C, 4 vol.% C2H6; the specific results are as follows Figure 1 , Figure 2 shown.

[0053] Figure 1 and Figure 2 The performance of CO2 isothermal capture and conversion integrated ethylene production of 6 different dual-functional materials is summarized, such as Figure 1 (a1)- Figure 2 As shown in (f1), the gas concentration data show that during the CO2 capture stage, the CO2 concentration rapidly increased from 0% to about 11% in the first 10 minutes of the reaction, and remained stable in the following 20 minutes. The concentration curve is similar to the typical reaction performance curve of CaO capturing CO2, which indicates that the capture of CO2 by the dual-functional composite material is mainly due to the effect of the CaO adsorbent. Figure 1 (a2)- Figure 2 As shown in (f2), there is no significant difference in the CO2 capture performance of the six spinel samples, and the adsorption capacity is about 0.26 g / g. At the same time, the CO2 capture performance of the six bifunctional materials did not decrease within 5 cycles. This is mainly due to the calcium-based adsorbent doped with 15 wt.% CeO2, which improves the material's anti-sintering performance. In addition, in the CO2 conversion stage, the doping of transition metal elements increased the CO2 conversion rate of the bifunctional material from 39.5% (Comparative Example 1) to 41.3% (Example 1), 66.3% (Example 2), 99.6% (Example 3), 55.0% (Example 4), and 62.8% (Example 5). This shows that doping with transition metal elements helps to activate CO2, which is consistent with Figure 1 (a2)- Figure 2 This is related to the increase in ethane conversion shown in (f2).

[0054] Figure 1 and Figure 2The ethane concentrations and ethane conversion rates of different bifunctional materials are also summarized. It can be found that the ethane concentration of the bifunctional material of Example 1 in the CO2 conversion stage can reach up to 3.7%; while the ethane concentration detected in the bifunctional material doped with transition metal elements is lower, about 0.5%-3.2%; the initial ethane conversion rates of the six samples are 24.3% (Comparative Example 1), 35.6% (Example 1), 41.9% (Example 2), 97.9% (Example 3), 32.4% (Example 4), and 44.7% (Example 5), respectively. The above results indicate that doping with transition metal elements increases the ethane conversion rate.

[0055] Moreover, doping with transition metals leads to a significant change in the selectivity of the product. As the number of cycles increases, the ethylene selectivity shows an upward trend.

[0056] Among them, the bifunctional material of Example 3 (NiMg50 sample) has low selectivity for ethylene, and high selectivity for CO (about 80%) and CH4. CO and CH4 are the main products of ethane reforming and cracking. The increase in CO and CH4 selectivity indicates that doping with transition metal elements improves the activation ability of the bifunctional material for CC and increases the degree of cracking and reforming reaction. Therefore, the bifunctional material NiMg50 sample prepared by the present invention can be used as a good CO2-dry reforming catalyst.

[0057] The best dual-functional material (Example 5) was subjected to a cyclic regeneration test at 650°C isothermal conditions, with a sample mass of 200 mg. The CO2 isothermal capture and conversion integrated regeneration conditions were: 650°C, 21% O2.

[0058] like Figure 3 As shown, with the increase of the number of cycles, the CO2 conversion rate of the bifunctional material obtained in Example 5 decreased from 62.8% to 40.9%, the ethane conversion rate decreased from 44.7% to 24.12%, the ethylene selectivity increased from 78.4% to 90.1%, and the ethylene yield was as high as 35.1%. Therefore, the bifunctional material doped with Zn in the present invention exhibits the best oxidative dehydrogenation performance, that is, doping with transition metal element Zn improves the CO2 isothermal capture and conversion integrated ethylene production performance of the bifunctional material. At the same time, the reaction activity of the bifunctional material of the present invention decreases with the increase of the number of cycles, but with the increase of the number of cycles to 10 times, the ethylene yield can still be maintained at 21.7%. And the bifunctional material obtained in Example 5 was regenerated for 1 hour in an air atmosphere at 650°C after 10 cycles, and the CO2 and ethane conversion rates can be restored to more than 90% of the original in the subsequent integrated test. This shows that the CO2 capture and utilization integrated bifunctional material of the present invention has good ethane oxidative dehydrogenation and cyclic regeneration performance.

[0059] At the same time, the dual-functional material of the present invention exhibits a high CO2 conversion rate and ethylene yield under mild conditions (isothermal adsorption at 650°C). The good oxidative dehydrogenation performance and simple operating conditions indicate that the present invention has good industrial application prospects.

[0060] In summary, the present invention provides a CO2 capture and utilization integrated dual-functional material and a preparation method and application, by doping transition metal elements into the chromium-based spinel catalyst, changing the charge distribution of the spinel, increasing the number of ethane active sites, reducing the energy barrier of the ethane and CO2 activation reaction, and facilitating the occurrence of the CO2-ethane oxidative dehydrogenation reaction. The present invention does not require the use of harsh conditions such as high pressure or airtightness, the preparation method is simple, the production process does not generate toxic and hazardous waste, and is suitable for large-scale industrial production.

[0061] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A CO2 capture and utilization integrated dual-function material, characterized in that: A mixture comprising an adsorbent and a catalyst in a mass ratio of 1:(0.5-1.5); The adsorbent is a calcium-based adsorbent or a calcium-based adsorbent doped with a metal oxide; The catalyst is a chromium-based spinel doped with transition metal elements.

2. The CO2 capture and utilization integrated dual-function material according to claim 1, characterized in that: The calcium-based adsorbent includes one or more of calcium oxide, calcium hydroxide, calcium carbonate and slaked lime; The metal oxide includes one or more of CeO2, MgO and Al2O3, and the mass doping ratio of the metal oxide in the adsorbent is less than 30%.

3. The CO2 capture and utilization integrated dual-function material according to claim 1, characterized in that: The transition metal elements doped in the catalyst include one or more of Fe, Co, Ni, Cu and Zn, and the molar doping ratio of the transition metal elements in the catalyst is less than 50%.

4. The CO2 capture and utilization integrated dual-function material according to claim 1, characterized in that: The particle size of the integrated dual-function material used for CO2 capture is 40-60 meshes.

5. The method for preparing the integrated dual-functional material for CO2 capture and utilization according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: mixing the adsorbent and the catalyst in proportion.

6. The method for preparing the CO2 capture and utilization integrated dual-functional material according to claim 5, characterized in that: Among the adsorbents, the preparation steps of the calcium-based adsorbent doped with metal oxides include: adding citric acid to a solution containing calcium nitrate and metal nitrate, heating and stirring until it is in a gel state, and obtaining a calcium-based precursor through aging; calcining the calcium-based precursor at 850-950° C. for 1.5-2.5 hours, and then grinding and screening to obtain the calcium-based adsorbent doped with metal oxides.

7. The method for preparing the integrated dual-functional material for CO2 capture and utilization according to claim 6, characterized in that: The ratio of the total molar amount of calcium ions in the calcium nitrate and the metal ions in the metal nitrate to the molar amount of citric acid is 1:(0.99-1.01); The preparation steps of the calcium-based adsorbent doped with metal oxides are as follows: the heating temperature for heating and stirring until the gel state is 75-85°C; the aging is performed at 100-110°C for 11-13 hours; and the heating rate of the calcination is 4-6°C / min.

8. The method for preparing the integrated dual-functional material for CO2 capture and utilization according to claim 5, characterized in that: The preparation steps of the chromium-based spinel doped with transition metal elements in the catalyst include: dissolving transition metal nitrate, magnesium nitrate, chromium nitrate and citric acid in deionized water, heating and stirring until gel-like, and obtaining a catalyst precursor through aging; calcining the catalyst precursor at 850-950° C. for 3.5-4.5 hours, and then grinding and screening to obtain the chromium-based spinel doped with transition metal elements.

9. The method for preparing the integrated dual-functional material for CO2 capture and utilization according to claim 8, characterized in that: The molar ratio of the transition metal nitrate, magnesium nitrate, chromium nitrate and citric acid is 1:1:4:6; The transition metal nitrate comprises one or more of ferrous nitrate, cobalt nitrate, nickel nitrate, copper nitrate and zinc nitrate; The molar volume ratio of the transition metal nitrate and deionized water is 6.25 mmol: (7-12) mL; In the preparation steps of the chromium-based spinel doped with transition metal elements, the heating temperature for heating and stirring until the gel state is 75-85° C.; the aging is performed at 140-160° C. for 11-13 hours; and the heating rate during calcination is 4-6° C. / min.

10. Integrated application of the dual-functional material according to any one of claims 1 to 4 in CO2 capture and ethane oxidative dehydrogenation to ethylene or ethane reforming / cracking.

Citation Information

Cited By

  • Method for efficiently preparing ethylene through concerted catalysis of ethane and carbon dioxide

    CN121800600A